Implementing person‐centred key performance indicators to strengthen leadership in community nursing: A feasibility study. (13th August 2020) - McCance, Tanya; Dickson, Caroline A. W.; Daly, Laura; Boomer, Christine A.; Brown, Donna; Lynch, Brighide; MacArthur, Juliet; Mountain, Kristina; McCormack, Brendan
Abstract: Aims: To explore the utility and feasibility of implementing eight person‐centred nursing key performance indicators in supporting community nurses to lead the development of person‐centred practice. Background: Policy advocates person‐centred health care, but few quality indicators exist that explicitly focus on evaluating person‐centred practice in community nursing. Current quality measurement frameworks in the community focus on incidences of poor or missed opportunities for care, with few mechanisms to measure how clients perceive the care they receive. Methods: An evaluation approach derived from work of the Medical Research Council was used, and the study was underpinned by the Person‐centred Practice Framework. Participatory methods were used, consistent with person‐centred research. Results: Data were thematically analysed, revealing five themes: giving voice to experience; talking the language of person‐centredness; leading for cultural change; proud to be a nurse; and facilitating engagement. Conclusions: The findings suggest that implementing the eight person‐centred nursing key performance indicators (KPIs) and the measurement framework is feasible and offers a means of evidencing person‐centredness in community nursing. Implications for Nursing Management: Person‐centred KPI data, used alongside existing quality indicators, will enable nurse managers to evidence a high standard of care delivery and assist in the development of person‐centred practice.